Optimizing Mediation as An Effort to Settle Marital Disputes in Court - Akhmad Kamil Rizani; Muchimah, Muchimah (Jurnal Ilmu Hukum Tambun Bungai, 2023)
This study discusses the Optimization of Mediation in the Resolution of Marriage Disputes in Court. Marriage is an essential event in human life as a legal and religious act. Along the household's journey as husband and wife, it is not uncommon for differences of opinion or principles between husband and wife to occur, which end up threatening the integrity of a marriage. Mediation as one of the Alternative Dispute Resolution (ADR) is seen as a humanist and equitable way of resolving disputes. Humanist because the decision-making mechanism (peace agreement) is the authority of the parties to the dispute and maintains good relations. Fair because each party negotiates options for resolving the problem. Divorce cases in religious courts are first required to be mediated; Mediation is carried out to resolve problems to reconcile the husband and wife. This study uses a normative juridical research method using a statutory approach that focuses on optimizing Mediation in the Resolution of Marriage Disputes in Court. The result of this study is that the optimization of Mediation in court cannot be separated in several ways, namely the Supreme Court, as part of law enforcement, which issued PERMA No. 1 of 2016 concerning mediation procedures in court, is the right step in resolving disputes, especially marital disputes. In addition, the role of competent mediators, cooperative parties, and reasonable legal culture. Keywords : Optimization, Mediation, Marriage Dispute